REVERSIBLY INACTIVATED HEAT-RESISTANT DNA POLYMERASE - KAWAMURA YOSHIHISA; KAWAKAMI FUMIKIYO; KOMATSUBARA YUSUKE (1998)
PROBLEM TO BE SOLVED: To obtain the subject new reversibly inactivated heat-resistant DNA polymerase modified with a dicarboxylic acid anhydride, not generating a nonspecific band, not forming the dimer of a primer, and useful as a reagent for amplifying nucleic acids, etc. SOLUTION: This new reversibly inactivated heat-resistant DNA polymerase modified with a dicarboxylic acid anhydride can eliminate problems on PCR, such as the generation of back grounds (nonspecific band) due to nonspecific amplification and the formation of a primer dimer, etc. The heat-resistant DNA polymerase is obtained by separating the chromosomal DNA of Thermus thermophilus HB8 by a conventional method, cleaving with a restriction enzyme, binding to a DNA, transforming Escherichia coli, selecting a colony having a DNA polymerase activity to obtain a gene, expressing the gene, and subsequently reacting the obtained heat-resistant DNA polymerase with 2,3- dimethylmaleic anhydride, etc.